Astrocytoma - Fahrul Amri (Universitas Syiah Kuala, 2009)
Abstnk. Astrocytoma merupakan tumor otak yang paling sering terjadi pada anak, dengan frekuensi lebih dari setengah jumlah keganasan pada sistem saraf primer. Insidensi tahunan mencapai 14 kasus baru per 1000000 anak dibawah usia 15 tahun. Diagnosis ditegakkan berdasarkan gejala klinis, pemeriksaan fisik, pemeriksaan CT scan dan pemeriksaan Head and spine MRI. Penanganan Astrocytoma disesuaikan dengan lokasi dan grade dari tumor tersebut. IO.year survival rate untuk astrocytoma cerebellar low-grade yang dapat diangkat lengkap mendekati 100%. (JKS 2009,·2:97-100)Kata Kunci : AstrocytomaAbstract. Astrocytoma is the most common brain tumor of childhood, more than 50% tumor on primary nervous system. Annual incident reach 14 new cases per 1:000.000 children under 15 years old, Diagnose is made based on clinical symptoms, physical examination, CT Scan and Head and Spine MRI. Management of Astrocytoma is based on the location and grade of the tumor. IO-year survival rate for low grade Cerebellar Astrocytomas, which are resected completely, is near 100%. (JKS 2009;2:97-100)Key word : Astrocytoma